Perancangan Sistem Informasi Pelayanan Masyarakat Pada Kantor Desa Negeri Agung Berbasis Web - Setiawan, Iwan (Jurnal Nasional Ilmu Komputer, 2024)
The Negeri Agung village is a place where administrative service activities are carried out. The Negeri Agung village office still carries out service activities manually, in which the community still has to come directly to the village office. Based on the results of this study, the researchers tried to design a web-based administrative service system using a prototype method to facilitate the community and village office staff in carrying out services. With this service system, it is hoped that it can assist village communities in registering anywhere and anytime without having to come to the village office